2010
DOI: 10.1177/0888406409360013
|View full text |Cite
|
Sign up to set email alerts
|

Book Talks in Special Education Methods Courses: Using Literature to Influence, Inspire, and Prepare Teacher Candidates

Abstract: An investigation on the use of literature as part of the teacher preparation process probed the impact of book talks on teacher candidates’ attitudes toward people with disabilities. Candidates in a 4-year undergraduate program participated in book talks reflecting subjects relevant to course work. Books reflected various effects of disability, including the impact on individuals or their families. Data were collected from written reflections and survey responses. Qualitative analysis revealed that the assignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
3
0
8
Order By: Relevance
“…A közösségi élmény erejének hatását rengeteg szöveghely támasztja alá a tanulmányokban. Fontos pontjai ezeknek, hogy a közös munka a felületes olvasásnál mélyebb, refleektívebb folyamat volt (Burbank et al, 2010), mely által közösen konstruált tudás jelent meg a csoportban (Robertson & Smith, 2017;Scheffeel et al, 2018), és amelyet a résztvevők kimondott an értékeltek (Marable et al, 2010;Robertson & Smith, 2017). Burbank és munkatársai (2010) a könyvklubban zajló tanulási folyamat (Hall és Mensah által is kiemelt) közösségi jellege mellett aktív jellegére is felhívják a fingyelmet.…”
Section: Dobrova Zita -Szivák Juditunclassified
See 2 more Smart Citations
“…A közösségi élmény erejének hatását rengeteg szöveghely támasztja alá a tanulmányokban. Fontos pontjai ezeknek, hogy a közös munka a felületes olvasásnál mélyebb, refleektívebb folyamat volt (Burbank et al, 2010), mely által közösen konstruált tudás jelent meg a csoportban (Robertson & Smith, 2017;Scheffeel et al, 2018), és amelyet a résztvevők kimondott an értékeltek (Marable et al, 2010;Robertson & Smith, 2017). Burbank és munkatársai (2010) a könyvklubban zajló tanulási folyamat (Hall és Mensah által is kiemelt) közösségi jellege mellett aktív jellegére is felhívják a fingyelmet.…”
Section: Dobrova Zita -Szivák Juditunclassified
“…A szépirodalom vagy a memoárok vagy azok a szakirodalmi szemelvények, amelyek anekdotikus elemet, történett é formálódó narratívát tartalmaznak, könnyebben teremtett ék meg a kapcsolatot az olvasó és a mű, a finkció és a saját tapasztalat között , hogy aztán a refleektív szakaszokban ezek együtt fogalmazódjanak meg. Számos olyan felismerésről olvashatunk a tanulmányokban, amikor a résztvevőkben megszületett a szereplőkkel való rokonság, hasonlóság, vagy a szereplők élethelyzetét, problémáit könnyen tudták saját példákkal vagy a gyakorlaton tanított diákok példáival szinkronizálni (Stanulis, 1999;Marable et al, 2010).…”
Section: Az éRzelmek éS a Motivációunclassified
See 1 more Smart Citation
“…If educators had an understanding about ASD from an aesthetic stance, through narrative fiction perhaps, and the educator lived through the experiences of someone with autism, then it is possible that the educator may adjust instructional practices (Winter-Messiers, et al, 2007), classroom and school management techniques (Osburne & Reed, 2011), as well as reconsider communication experiences (Nielsen, 2011) in order to meet the needs of students with ASD. Though empirical research supports the notion of using narrative fiction to help readers empathize with others (Brindley & Laframboise, 2002;Marable, Leavitt-Noble, & Grande, 2010), only a few research studies demonstrate how fiction can be a conduit to help pre-service teachers understand students with an ASD (e.g., Hughes, Hunt-Barron, Wagner, & Evering, 2014). A large gap within the literature regarding pre-service teachers' perceptions about ASD (Park, Chitiyo, & Choi, 2010) is evident.…”
Section: Fictional Narratives As a Conduit For Understandingmentioning
confidence: 99%
“…(continued) (i.e., using memoirs) increased attitudes, empathy, and respect toward people with disabilities (Marable et al, 2010), and simulated interactions between candidates and paraprofessionals suggested that inclusion instruction in coursework translates poorly to more authentic settings (Dotger & Ashby, 2010).…”
Section: Dispositionsmentioning
confidence: 99%